2016
DOI: 10.1186/s13075-016-1072-4
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variations in clinical symptoms and concentrations of inflammatory cytokines, melatonin, and cortisol in polymyalgia rheumatica before and during prednisolone treatment: a controlled, observational, clinical experimental study

Abstract: BackgroundIn contrast to rheumatoid arthritis (RA), no systematic investigation of diurnal variation has been carried out in polymyalgia rheumatica (PMR). The aim of the study was to provide the often-requested documentation of the 24-h time course of clinical symptoms in PMR and relate them to concentrations during the day of melatonin, inflammatory cytokines, and cortisol. Furthermore, the effects of 14 days of prednisolone treatment were studied.MethodsTen glucocorticoid-naive patients newly diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 46 publications
(94 reference statements)
0
20
0
1
Order By: Relevance
“…Cross reaction with N‐acetyl serotonin was 1% and 0.07% for 5‐methoxy tryptamine. A study using this assay reported daytime levels of approximately 5 pg/mL and 10 pg/mL …”
Section: Melatonin Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross reaction with N‐acetyl serotonin was 1% and 0.07% for 5‐methoxy tryptamine. A study using this assay reported daytime levels of approximately 5 pg/mL and 10 pg/mL …”
Section: Melatonin Measurementmentioning
confidence: 99%
“…Cross reaction with N-acetyl serotonin was 1% and 0.07% for 5-methoxy tryptamine. A study using this assay reported daytime levels of approximately 5 pg/mL 51 Circadian melatonin secretion (pg/mL, mean ± SD) was measured in the plasma samples of 12 healthy subjects using GC-NCI-MS…”
Section: Serum/plasma Riasmentioning
confidence: 99%
“…A recent clinical experimental study further supports the use of chronotherapy in PMR. 9 Although the formal criteria of non-inferiority were not met, our study showed a clear trend for a favourable clinical effect of MR prednisone over IR prednisone in patients with PMR. Further confirmation should be sought from a large clinical trial in patients with PMR, with careful consideration of inclusion and response criteria, based on the present study experience.…”
Section: Discussionmentioning
confidence: 53%
“…The relationship between MS and sleep impairment is bi-directional, with inflammation as only one of the involved factors. The abrupt onset of PMR during nighttime rest that is much more frequent in PMR patients than in SEORA patients and the possible role of other, different inflammation mediators can explain the discrepancy between MS and CRP concentrations [39].…”
Section: Discussionmentioning
confidence: 99%